Growth after the crisis - Rodrik, Dani ([s.n.] [S.l.], 2009)
Provides an interpretation of growth performance in the world economy since the end of the Second World War. Argues that the engine of growth has been rapid structured change in the developing nations and that structural transformation was facilitated by 'productivist' policies in successful countries. Examines how the contours of the world economy post-crisis is likely to affect this process. Suggests that the threat of a lower demand for imports from developing countries can be averted by their employing more balanced growth strategies which allow consumption of tradables to expand alongside production.